Evaluating the Effects of Offshoring and Technology on the Rising Skill Premium – Literature Review - Katev, Stefan (2013)
Rapid technological progress and innovation have enabled the world economy to enter its second golden age of globalization, however, unprecedented in the levels of economic integration and interdependence. Development in the information and telecommunication technologies and transportation allowed to segregate geographically different stages of production and services, thus allowing for greater specialization, operational cost reduction and increase in overall productivity. This process has, however, claimed to have harmed the low-skilled workers by reducing their earnings, while benefiting the high-skilled workers whose returns have increased. On the other hand, increase in the skill premium can be result of higher demand for skilled workers as a result of skill-biased technological change such as the resent ICT revolution. The aim of this paper is to discuss some of the most prominent models of offshoring which claim to be able explain the evolution of the skill premium in representative industrialized countries.